Preparation and characterisation of an 57Fe enriched haemoglobin spike material for species-specific isotope dilution mass spectrometry. Issue 9 (31st March 2016) - Brauckmann, C.; Frank, C.; Schulze, D.; Kaiser, P.; Stosch, R.; Swart, C.
Abstract : A species-specific ID-ICP-MS method for intact haemoglobin was developed applying an 57 Fe enriched haemoglobin spike, which was prepared and characterised carefully. Abstract : Haemoglobin (HGB) and its various isoforms are powerful markers for diagnostic and treatment control. For the first time a species-specific isotope dilution mass spectrometry (IDMS) method for the quantification of the whole protein without peptide digestion was developed in this study. The required species-specific HGB spike material was prepared by substituting the entire protohaem containing nat Fe for the same group enriched with 57 Fe. The spike material was characterised regarding isotopic enrichment and structural modification compared to natural HGB. Two different separation methods using a MonoQ® ion exchange chromatography column and a size exclusion column (SEC), respectively, have been developed for the separation of HGB from the matrix and their results for the quantification using IDMS were compared. For this, a high-performance liquid chromatography (HPLC) system was linked to an inductively coupled plasma mass spectrometer (ICP-MS) and HGB was quantified via its iron content. The IRMM/IFCC-467 and JCCRM 912-2 reference materials were used as control samples and for comparison of both separation techniques (MonoQ® and SEC). The HGB values obtained for both methods were found to be identical within the expanded uncertainty.